Effects of Technology Adoption, E-Commerce, and Process Efficiency on Agribusiness Supply Chain Performance - Aulia, Muhammad Reza; Sihombing, Dina Agnesia; Jakiyah, Ulpah; Astuti, Enny Diah; Sulaminingsih, Sulaminingsih (Universitas Negeri Gorontalo, 2024)
Digital transformation in the agricultural sector has become an essential driver of agribusiness supply chain improvement, particularly in regions facing structural productivity challenges such as West Java. This study specifically aims to examine how agricultural technology adoption, e-commerce utilization, and process efficiency influence agribusiness supply chain performance, while explicitly identifying the extent to which digital-based practices strengthen operational integration among agribusiness actors. Unlike previous studies that focus only on one or two aspects of digitalization, this research offers novelty by simultaneously analyzing three key digital transformation dimensions and empirically testing their combined contribution to agribusiness supply chain performance in a developing-country context. Using a quantitative survey approach involving 120 agribusiness respondents selected through purposive sampling, the study employs multiple linear regression to validate the proposed model. The findings show that technology adoption significantly enhances productivity and accuracy in land and resource management; e-commerce utilization expands market reach and improves transaction efficiency; and process efficiency accelerates product flow within the supply chain. All classical assumption tests confirm the model’s validity and reliability. This research contributes new empirical evidence on how integrated digital transformation initiatives strengthen agribusiness supply chain performance, offering practical insights for policymakers, agro-entrepreneurs, and digital agriculture developers.